2019
DOI: 10.1515/ntrev-2019-0054
|View full text |Cite
|
Sign up to set email alerts
|

Arc erosion behavior of TiB2/Cu composites with single-scale and dual-scale TiB2 particles

Abstract: Arc erosion behaviors of TiB2/Cu composites with single-scale and dual-scale TiB2 particles fabricated by powder metallurgy were studied. It was revealed that the dual-scale TiB2/Cu composites had fewer structure defects compared with the single-scale TiB2/Cu composites, and TiB2 particles with different size were uniformly distributed in the copper matrix. When the ratio of 2 μm over 50 μm TiB2 particles is 1:2, the density of TiB2/Cu composite is 98.5% and shows best mechanical and thermal properties. The ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…A uniform, stable, highly ordered and controllable nanoparticle film can be prepared by self-assembly method [26], which can improve the reproducibility and sensitivity of SERS detection. A previous study reported that the annealed Ag-Zr film deposited on polyimide (PI) can produce a new type of particle/film structure [27], which is significantly different from the traditional granular film [28][29][30][31]. Considering that the Ag nanoparticles spontaneously formed on the surface of the annealed Ag-Zr alloy films and the nanophase effects in copper alloys [27,[32][33][34][35][36][37], we attempt to selfgrown Ag nanoparticles with different morphologies on the surface of the deposited Mo-Ag alloy films by adjusting the Ag content at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…A uniform, stable, highly ordered and controllable nanoparticle film can be prepared by self-assembly method [26], which can improve the reproducibility and sensitivity of SERS detection. A previous study reported that the annealed Ag-Zr film deposited on polyimide (PI) can produce a new type of particle/film structure [27], which is significantly different from the traditional granular film [28][29][30][31]. Considering that the Ag nanoparticles spontaneously formed on the surface of the annealed Ag-Zr alloy films and the nanophase effects in copper alloys [27,[32][33][34][35][36][37], we attempt to selfgrown Ag nanoparticles with different morphologies on the surface of the deposited Mo-Ag alloy films by adjusting the Ag content at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…When a sufficient electric field is supplied between electrodes, the free primary electrons for the generation of the electron avalanche can be released from the cathode, such as by photoelectric emission, by ion impacts, by thermionic emission, and by field emission 40,41 . Figure 7A displays the schematic of the electron avalanche process.…”
Section: Resultsmentioning
confidence: 99%
“…There are many reasons leading to this result, which can be roughly concluded into two categories according to its characters. One is the different stress states, as original compressive stress can prevent the structure from loosening [25,26], which will reduce the erosion. The other category is the different surface morphologies that can change the character of the connection between the stationary and movable contacts [27,28].…”
Section: Effects Of Post-treatments On Arc Erosion Resistancementioning
confidence: 99%